Mortality of Post-COVID-19 Condition: 2025 Update - Giuseppe Lippi; Fabian Sanchis-Gomar (COVID)
Background: The coronavirus disease 2019 (COVID-19) pandemic has generated profound health, societal, and economic consequences, which have been further compounded by long-term sequelae commonly referred to as post-COVID-19 or long-COVID syndrome. Understanding the real-world impact of post-COVID-19 mortality is therefore critical for effective healthcare planning and resource allocation. Methods: A descriptive epidemiological study was conducted using data from the US National Center for Health Statistics 2018–2024 to identify deaths attributed to the post-COVID-19 condition, as classified by the ICD-10 code U09.9, from October 2021 to December 2024. Demographic factors such as gender, age, and place of death were also extracted. Results: By December 2024, 2653 US deaths were classified under the ICD-10 code U09.9, corresponding to an age-adjusted mortality rate of 0.089 × 100,000. Mortality was significantly higher in males compared to females (0.098 vs. 0.081 × 100,000; p < 0.001). A clear age-related mortality gradient was observed, with rates increasing almost linearly with advancing age. The largest fraction of post-COVID-19 deaths occurred at home (33.0%), followed by nursing homes (26.3%) and medical facilities (24.1%). Conclusions: These findings highlight the substantial yet complex impact of the post-COVID-19 condition on mortality, with higher rates observed in males, older adults, and individuals at home, highlighting the need for targeted healthcare interventions and resource allocation, particularly for these higher-risk groups.